2015
DOI: 10.1186/s12864-015-1981-7
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Ixodes ricinus genome sequencing with transcriptome and proteome annotation of the naïve midgut

Abstract: BackgroundIn Europe, Ixodes ricinus ticks are the most important vectors of diseases threatening humans, livestock, wildlife and companion animals. Nevertheless, genomic sequence information is missing and functional annotation of transcripts and proteins is limited. This lack of information is restricting studies of the vector and its interactions with pathogens and hosts. Here we present and integrate the first analysis of the I. ricinus genome with the transcriptome and proteome of the unfed I. ricinus midg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…Thus, the sequencing of the whole R. microplus genome is proceeding with only preliminary data published to date including several BAC clones and the mitochondrial genome of the Deutsch Texas R. microplus strain . Recently, preliminary genome sequence data for Ixodes ricinus were reported with ~998 million paired‐end reads (~47× coverage, approximately 63% of the total coding sequences) from Ilumina Inc, San Diego, CA, USA HiSeq™ next‐generation sequencing (GenBank Accession Numbers: and ) . Due to the complexity of tick genomes, EST and next‐generation transcriptome sequencing projects have been undertaken to inform researchers in terms of the identity of specific genes up‐regulated by different organs in feeding ticks, particularly salivary glands (sialome) and/or the mid‐guts (mialome).…”
Section: Reverse Genetics Approach To Tick Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the sequencing of the whole R. microplus genome is proceeding with only preliminary data published to date including several BAC clones and the mitochondrial genome of the Deutsch Texas R. microplus strain . Recently, preliminary genome sequence data for Ixodes ricinus were reported with ~998 million paired‐end reads (~47× coverage, approximately 63% of the total coding sequences) from Ilumina Inc, San Diego, CA, USA HiSeq™ next‐generation sequencing (GenBank Accession Numbers: and ) . Due to the complexity of tick genomes, EST and next‐generation transcriptome sequencing projects have been undertaken to inform researchers in terms of the identity of specific genes up‐regulated by different organs in feeding ticks, particularly salivary glands (sialome) and/or the mid‐guts (mialome).…”
Section: Reverse Genetics Approach To Tick Vaccinesmentioning
confidence: 99%
“…For example, the genome sizes for I. scapularis and R. microplus were estimated at 2Á1 and 7Á1 Gb, respectively, with repetitive sequences occurring in a mixture of long and short period interspersions with 65-80% of the DNA following a pattern of short period interspersions (70). Since this publication in 2005, the I. scapularis genome assembly was reported at 3Á89 coverage from 369 495 scaffolds built using 570 637 contigs with a total number of 20 486 coding genes (GenBank Accession: ABJB000000000.1 Ixodes scapularis strain Wikel colony (71) (76). Due to the complexity of tick genomes, EST and next-generation transcriptome sequencing projects have been undertaken to inform researchers in terms of the identity of specific genes up-regulated by different organs in feeding ticks, particularly salivary glands (sialome) and/or the mid-guts (mialome).…”
Section: Tick Genomic and Sequence Resourcesmentioning
confidence: 99%
“…Although our understanding of tick-pathogen interactions is still limited, advances in this field are facilitated by the increasing number of available genomic resources, including metabolomics, transcriptomics, and proteomics datasets of various ticks and tick-borne pathogens (TBPs) (Nene et al, 2004; Ayllón et al, 2015a; Cramaro et al, 2015; Kotsyfakis et al, 2015; Villar et al, 2015a; Gulia-Nuss et al, 2016; de Castro et al, 2016), and the recently published genome from Ixodes scapularis , a vector of Borrelia burgdorferi and Anaplasma phagocytophilum in North America (Gulia-Nuss et al, 2016). Together with tools such as tick cell lines and the widespread adaptation of RNA interference (RNAi) to study tick gene function (Bell-Sakyi et al, 2007; de la Fuente et al, 2007), this has opened exciting possibilities to identify determinants affecting tick vector competence.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies have investigated gene expression in the tick salivary glands and/or the tick midgut because these tissues are critical for pathogen transmission [12,13,14,16]. Taken together these studies have shown that there are thousands of transcripts that are differentially expressed with respect to the duration 70 of the blood meal, the developmental stage (nymph versus adult), the specific tissue (salivary glands versus midgut), and other conditions [12,13,18,16,14,15,17,19]. Most of these studies have focused on gene expression during the blood meal in either the nymphal tick or the adult tick, which is when pathogen transmission occurs.…”
mentioning
confidence: 99%
“…These RNA sequencing studies can also provide information on genetic variation within and among populations [11]. To date, several studies have investigated gene expression in I. ricinus [12,13,14,15,16,17]. Most of these studies have was expected to show low heterozygosity.…”
mentioning
confidence: 99%